Serum drug levels to diagnose non-adherence in acute decompensated heart failure - Solar, Miroslav; Pelouch, Radek; Vorisek, Viktor; Furmanova, Vera; Ceral, Jiri (Biomedical papers, 2016)
Background: The aim of this study was to analyze medication non-adherence by measuring serum drug levels (SDL) in patients presenting with acute decompensated heart failure (ADHF).Methods: Included in the study were chronic heart failure patients presenting with signs of acute decompensation. Blood sampling for the measurement of SDL was performed shortly after presentation. SDL were measured using liquid chromatography coupled with mass spectrometry. The estimation of SDL was calculated from the recommended chronic cardiac medications with the exception of drugs administered as part of the acute treatment prior to blood sampling. The patients were labeled as non-adherent when any one of the evaluated medications was not found in the serum.Results: Fifty patients with ADHF were prospectively enrolled. All of the evaluated drugs were detected in the sera of 28 (56%) patients. Non-adherence was diagnosed in the remaining 22 (44%) patients. None of the evaluated medications was detected in the sera of 5 (10%) patients.Conclusion: The estimation of SDL indicates that non-adherence to the recommended chronic therapy is a common problem among patients presenting with ADHF. This method should be an essential aspect of routine clinical evaluation in these patients.
Keywords: acute heart failure; drug non-adherence; pharmacotherapy; serum drug levels